Clinical evaluation of an automated, rapid mariPOC antigen test in screening of symptomatics and asymptomatics for SARS-CoV-2 infection - Gunell Marianne; Rantasärkkä Kaisa; Arjonen Rita; Sanden Antti; Vuorinen Tytti (WILEY, 2022)
A novel automated mariPOC SARS-CoV-2 antigen test was evaluated in a Health Care Center Laboratory among symptomatic and asymptomatic individuals seeking SARS-CoV-2 testing. According to the national testing strategy, reverse transcription polymerase chain reaction (RT-PCR) was used as a reference method. A total of 962 subjects were included in this study, 4.8% (46/962) of their samples were SARS-CoV-2 RT-PCR-positive, and 87% (40/46) of these were from symptomatics. Among the symptomatics, the overall sensitivity of the mariPOC SARS-CoV-2 test was 82.5% (33/40), though the sensitivity increased to 97.1% (33/34) in samples with a C-t < 30. The mariPOC SARS-CoV-2 test detected two of six PCR-positive samples among the asymptomatics, four cases that remained antigen test negative had C-t values between 28 and 36. The specificity of the mariPOC SARS-CoV-2 test was 100% (916/916). The evaluation showed that the mariPOC SARS-CoV-2 rapid antigen test is very sensitive and specific for the detection of individuals who most probably are contagious.